KPI5 Is Involved in the Regulation of the Expression of Antibacterial Peptide Genes and Hemolymph Melanization in the Silkworm, Bombyx mori - Heng, Jingya; Liu, Huawei; Xu, Jiahui; Huang, Xuan; Sun, Xiaotong; Yang, Runze; Xia, Qingyou; Zhao, Ping (Frontiers in Immunology, 2022)
Kunitz-type protease inhibitors (KPIs) are ubiquitously found in many organisms, and participate in various physiological processes. However, their function in insects remains to be elucidated. In the present study, we characterized and functionally analyzed silkworm KPI5. Sequence analysis showed that KPI5 contains 85 amino acids with six conserved cysteine residues, and the P1 site is a phenylalanine residue. Inhibitory activity and stability analyses indicated that recombinant KPI5 protein significantly inhibited the activity of chymotrypsin and was highly tolerant to temperature and pH. The spatio-temporal expression profile analysis showed that KPI5 was synthesized in the fat body and secreted into the hemolymph. In vivo induction analysis showed that the expression of KPI5 in the fat body was significantly upregulated by pathogen-associated molecular patterns (PAMPs). Binding assays suggested that KPI5 can bind to pathogens and PAMPs. In vitro pathogen growth inhibition assay and encapsulation analysis indicated that KPI5 can neither kill pathogenic bacteria directly nor promote the encapsulation of agarose beads by silkworm hemocytes. Recombinant protein injection test and CRISPR/Cas9-mediated knockdown showed that KPI5 promotes the expression of antimicrobial peptides (AMPs) in the fat body. Moreover, the survival rate of individuals in the KPI5 knockdown group was significantly lower than that of the control group after pathogen infection. Phenoloxidase (PO) activity assays showed that KPI5 significantly inhibited the hemolymph PO activity and melanization induced by PAMPs. These findings suggested that KPI5 plays a dual regulatory role in innate immunity by promoting the expression of antimicrobial peptides in the fat body and inhibiting hemolymph melanization. Our study furthers the understanding of the function of insect KPIs and provides new insights into the regulatory mechanism of insect immune homeostasis.